Patient outcomes and amotosalen/UVA‐treated platelet utilization in massively transfused patients. Issue 3 (15th February 2017) - Nussbaumer, W.; Amato, M.; Schennach, H.; Astl, M.; Chen, C. Y.; Lin, J.‐S.; Corash, L.; Benjamin, R. J.
Abstract : Background: Amotosalen/UVA‐treated platelet concentrates (PCs) have demonstrated efficacy for treating and preventing bleeding in clinical trials and in routine use; however, most studies were performed in haematology/oncology patients. We investigated efficacy during massive transfusion (MT) in general hospitalized patients. Methods: Universal amotosalen/UVA treatment (INTERCEPT Blood System) of platelets was introduced at a large Austrian medical centre. We performed a retrospective cohort analysis comparing component use, in‐hospital mortality and length of stay after MT that included platelet transfusion, for two periods (21 months each) before and after implementation. Results: A total of 306 patients had MT. Patients were mostly male (74%) and ≥18 years old (99%), including 93 liver transplant, 97 cardiac or vascular surgery and 51 trauma patients. There were no differences in demographics between the periods. Component use on the day and within 7 days of the MT event was unchanged post‐IBS implementation, except trauma patients received fewer RBCs on the day. The mean ratio of RBC:platelets:plasma on the day of the MT was close to 1:1:1 in both periods, except for liver transplants with MT who received more plasma components. Overall, in‐hospital mortality (preimplementation = 27·6% vs. postimplementation = 24·0%; P = 0·51) and median time to discharge (preimplementation = 27 vs. postimplementation = 23 days; P = 0·37) did not change, except for cardiac and vascular surgery patients who were discharged earlier. Conclusion: The introduction of amotosalen/UVA‐treated, pathogen‐reduced PC did not adversely affect clinical outcomes in massively transfused patients in terms of blood product usage, in‐hospital mortality and length of stay for a range of clinical indications for platelet transfusion support.